Freedom to care : liberalism, dependency care, and culture - Bhandary, Asha L. (New York, NY : Routledge, 2020)
This book presents the first systematic account of dependency care in a liberal theory of justice. Despite the fact that receiving dependency care is necessary for human survival, the practices with which we meet society's care needs are seldom recognized for their functional role. Instead, norms about gender and race obscure and shape expectations about whose needs for care are legitimate as well as about whose caregiving labor more advantaged members of society will receive. These opaque arrangements must be made visible if we are to remedy skewed intuitions and judgements about care. Freedom to Care develops a modified form of social contract theory with which to evaluate society's caregiving arrangements. Building on work by feminist liberals and care ethicists, it reframes debates about care to move beyond gender with an inequality-tracking framework that can be employed in any culture. Because care provision has been enmeshed in the subordination of women and people of color, eliminating the invisibility of these forms of labor yields a critical liberal theory of justice with feminist and anti-racist aims.
OCLC-licensed vendor bibliographic record.
Keywords: Dependents -- Care; Dependents -- Care -- Social aspects; Caregivers -- Cross-cultural studies; Liberalism; PHILOSOPHY / Political; PHILOSOPHY / Ethics & Moral Philosophy